2021
DOI: 10.3390/vaccines9101151
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Response to SARS-CoV-2 Vaccine of a Patient Receiving Methotrexate Treatment and Implications for the Need of Monitoring

Abstract: We report a case of monitoring the antibody response to the BioNTech–Pfizer vaccine of a 50-year-old female diagnosed with rheumatoid arthritis undergoing treatment with methotrexate (MTX). Antibody levels were measured 21 days after dose 1 (i.e., on the day of dose 2) and then 8, 14 and 30 days after dose 2 with Elecsys Anti-SARS-CoV-2 S assay (Roche Diagnostics). Patient showed a negative result after dose 1 and had the serum sample retested using a LIAISON® SARS-CoV-2 TrimericS IgG assay (DiaSorin), which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…We did not observe Methotrexate as an obstacle for obtaining an optimal medium-term response to mRNA vaccines. Discrepancies exists in previous studies evaluating the effect of this drug in the short-term response to vaccines 26 , 27 . In our series, no subject under Methotrexate had received Glucocorticoids and we did not detect a decrease in its nAB titre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not observe Methotrexate as an obstacle for obtaining an optimal medium-term response to mRNA vaccines. Discrepancies exists in previous studies evaluating the effect of this drug in the short-term response to vaccines 26 , 27 . In our series, no subject under Methotrexate had received Glucocorticoids and we did not detect a decrease in its nAB titre.…”
Section: Discussionmentioning
confidence: 99%
“…A poor humoral immune response has also been described for SLE patients treated with Glucocorticoids and immunosuppressive drugs after a single dose of mRNA vaccines 24 . SLE patients under Methotrexate or Mycophenolate-Mofetil regimes have also showed a lower antibody response against SARS-CoV-2 fifteen days after the second dose 25 , although current evidence about the effect of Methotrexate on humoral response is not consistent 26 , 27 . None of the works mentioned above evaluated nAB as a measure of response to the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Haberman et al reported that patients with immune-mediated inflammatory diseases (IMIDs) on background MTX achieved anti-S antibodies production in only 62.2% of cases, whereas healthy subjects and patients with IMIDs on biologic treatments demonstrated robust antibody responses (over 90%) after primary vaccination (two doses, a 3-week interval) with the BNT162b2 mRNA COVID-19 vaccine [ 5 ]. Lukaszuk et al monitored anti-S antibody titers in a female patient with RA taking MTX and in 119 HCWs for 180 days after the second dose of the BNT162b2 mRNA COVID-19 vaccine using the same assay kit (Roche Elecsys Anti-SARS-CoV-2 S) that we used [ 7 ]. In this study, on the 8th day after the second vaccination dose, 68.1% of HCWs had results above 2500 U/mL, which is the upper detection limit of the assay set by Lukaszuk et al The participants whose results were detected within the upper limit had an average antibody titer of 1670.6 U/mL on day 8, 1319.0 U/mL (21% decrease) on day 14, and 845 U/mL (35% decrease) on day 30 after the second dose.…”
Section: Discussionmentioning
confidence: 99%
“…Lukaszuk et al continued to monitor anti-S antibody titers and reported that anti-S antibody titers gradually increased to a maximum of 3 months (203,7 U/mL), were maintained for up to 4 months (201.0 U/mL), and decreased slightly at 6 months (147.2 U/mL) after the second vaccination in patient with RA taking MTX [ 7 ]. In contrast, in HCWs, the anti-S antibody titers continued to decrease after the second vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…al. [28] mRNA vaccine 126 patients with Li et al [36] CoronaVac, Lukaszuk et al [37] BNT162b2 vaccine (mRNA vaccine)…”
Section: Spinelli Etmentioning
confidence: 99%